Systemic lupus erythematosus and atherosclerosis: immune pathways and the uncharted territory of gut microbiota and metabolism - Pan, Quanren; Huang, Xuemei; Liu, Chaobin; Pan, Qingjun; Huang, Shian (Frontiers in Immunology, 2025)
Patients with Systemic Lupus Erythematosus (SLE) are significantly more susceptible to atherosclerosis, which may elevate their mortality risk. The review explores recent understandings of the origins and remedies for atherosclerosis associated with SLE. Our focus is particularly on the consequences of immune system disparities, interruptions in intestinal bacteria, and metabolic complications. The influence of SLE on atherosclerosis extends past usual risk elements, including processes specific to the disease. The list encompasses excessive immune cell activity, production of autoantibodies, inflammatory responses. A variety of therapies for atherosclerosis linked to SLE encompass cholesterol-lowering medications, anti-inflammatory drugs, immune suppressors, antimalarials, interferon treatments, NET inhibitors, and methods aimed at T and B-cells. However, existing research has its shortcomings, necessitating additional clinical trials to ascertain the efficacy and security of these therapies. The direct interactions among SLE, gut microbiota, metabolism, and atherosclerosis is underexplored, presenting innovation opportunities. Research into specific gut microbial strains and metabolites’ effects on immune responses and atherosclerosis progression in SLE patients is needed. Such research could uncover novel therapeutic targets and biomarkers, advancing prevention and treatment strategies for SLE cardiovascular complications.